2011
DOI: 10.1177/0021998311401090
|View full text |Cite
|
Sign up to set email alerts
|

Pultruded glass fiber- and pultruded carbon fiber-reinforced chemically bonded phosphate ceramics

Abstract: The main goal of this article is to present the pultrusion process for glass fiber-and carbon fiber-reinforced chemically bonded phosphate ceramics (CBPCs). Samples were fabricated with 15% of fibers by volume. An improvement (with respect to the matrix) of 29 times for the bending strength of CBPCs pultruded graphite fibers composites and 17 times for CBPCs pultruded glass fiber composites is shown. Bending strength was obtained with the three-point bending test. The CBPCs were fabricated by mixing special fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…7,8 In the field of composite materials multiple materials such as fillers and reinforcements have been combined with these cements. [9][10][11][12] As Wollastonite powder and the phosphoric acid are mixing, the metal oxides dissolve in the acid, followed by an exothermic acid-base reaction, generating a dense paste that hardens in crystalline phases without the need of thermal processing, and thus forming calcium phosphate cement. [13][14][15] Three chemical equations have been proposed to explain the different reaction products of the mixture of phosphoric…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In the field of composite materials multiple materials such as fillers and reinforcements have been combined with these cements. [9][10][11][12] As Wollastonite powder and the phosphoric acid are mixing, the metal oxides dissolve in the acid, followed by an exothermic acid-base reaction, generating a dense paste that hardens in crystalline phases without the need of thermal processing, and thus forming calcium phosphate cement. [13][14][15] Three chemical equations have been proposed to explain the different reaction products of the mixture of phosphoric…”
Section: Introductionmentioning
confidence: 99%
“…The world today demands new technologies for the production of ceramics that enable the industry to optimize the energy consumption and to minimize wastes by using them in other applications or processes. This is the case of using alternative ceramic materials like phosphates and geopolymers to hold large amount of wastes [10,11], traditional building materials with similar goals [12], or developing new manufacturing processes that use these unutilized materials [13]. Particularly in the processing, there is a limitation in the feasibility of traditional technology-related methods to produce complex-shaped ceramic-based parts with the desired compositions, microstructures and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Colorado et al had carried out intensive research on this type of CBPC composite. Higher performance structure CBPC composites were manufactured with the reinforcements, for instance, nano-fibers, graphite nanoplatelets (GNPs) [ 15 ], glass fiber and carbon fiber [ 16 ]. The results from Colorado’s studies showed that the different fibers improved the properties of CBPC composites at different ranges.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interfaces between CBPC matrix and crystalline phases looks almost cracked, it should be conducted more research to improve the adhesion [ 15 ]. For the CBPC prepared by pultrusion method, the bending strength increased by a factor of 29 and 17 for pultruded carbon fiber and pultruded glass-fiber reinforcement CBPCs [ 16 ]. However, the pultrusion technique is complicated and higher cost.…”
Section: Introductionmentioning
confidence: 99%